Changes in biomechanical properties of the cornea after modified transepithelial crosslinking - I. B. Medvedev; V. Ju. Evgrafov; S. N. Bagrov; R. S. Kemov; N. N. Dergacheva (Oftalʹmologiâ, 2016)
The aim of the study was to evaluate changes in biomechanical properties of the cornea after conducting transepithelial crosslinking with the prior application of a 40 % glucose solution.Materials and methods. Just studied the biomechanical properties of the corneas of six rabbits breed Chinchilla (12 eyes). 4 rabbit entered in the experimental group, in which in one eye glucose solution was applied on the cornea and allowed to stay for 10 minutes, followed by the instillation of 0.1 % Riboflavin solution for 30 minutes. On a couple of the rabbit eye was applied a solution of Riboflavin without prior instillation of glucose. Then carried out the procedure of irradiation according to the conventional technology with UV with a wavelength of 370 μm and a beam energy of 3.0 mW / cm2. Two rabbits (4 eyes) were included in the control group, in which crosslinking was not performed. After 1 month the euthanasia of the animals was performed with subsequent enucleation for corneal research on a tensile testing machine. In the control and experimental group compared, the relaxation curves and the following parameters were analyzed: initial stress (MPa), equilibrium stress (MPa) modulus of elasticity.Results and their discussion. After the crosslinking the rise of the initial stress (in the control group and 0.7+0.1 MPa, in the experimental and 1.5+0.2 1.3+0.3 MPa, respectively). The stress relaxation is fast (equilibrium stress value is reached after 250 sec.) and after the administration of glucose for approximately 75 seconds, which means a greater rigidity of experimental group of samples. In the experimental groups significantly changed and the modulus of elasticity: its value has increased approximately in 2 times in comparison with control samples. The equilibrium stress values in the experimental groups were different from the zero value that also indicates a change in the chemical structure of the samples.Conclusions. Holding transepithelial of crosslinking with prior instillation of a 40 % solution of glucose facilitates the penetration of Riboflavin into the corneal stroma and improves its biomechanical strength. Our data indicate promising application in the clinic of this modification of transepithelial crosslinking.